Giúp mình với cảm ơn trước ạ

Question

Giúp mình với cảm ơn trước ạ
giup-minh-voi-cam-on-truoc-a

in progress 0
Edana Edana 8 tháng 2020-10-29T04:50:45+00:00 2 Answers 55 views 0

Answers ( )

  1. Giải thích các bước giải:

    Ta có:

    \(\begin{array}{l}
    1,\\
    a,\\
    \sqrt {81}  – \sqrt {80} .\sqrt {0,2}  = \sqrt {81}  – \sqrt {80.0,2}  = \sqrt {81}  – \sqrt {16}  = \sqrt {{9^2}}  – \sqrt {{4^2}}  = 9 – 4 = 5\\
    b,\\
    \sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}}  – \dfrac{1}{2}\sqrt {20}  = \left| {2 – \sqrt 5 } \right| – \dfrac{1}{2}\sqrt {{2^2}.5}  = \left( {\sqrt 5  – 2} \right) – \dfrac{1}{2}.2.\sqrt 5  = \sqrt 5  – 2 – \sqrt 5  =  – 2\\
    2,\\
    a,\,\,\,\,\,\,\,\,\,\,\sqrt { – x + 1} \\
    DKXD:\,\,\,\, – x + 1 \ge 0 \Leftrightarrow  – \left( {x – 1} \right) \ge 0 \Leftrightarrow x – 1 \le 0 \Leftrightarrow x \le 1\\
    b,\,\,\,\,\,\,\,\sqrt {\dfrac{1}{{{x^2} – 2x + 1}}} \\
    DKXD:\,\,\,\,\left\{ \begin{array}{l}
    \dfrac{1}{{{x^2} – 2x + 1}} \ge 0\\
    {x^2} – 2x + 1 \ne 0
    \end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}
    \dfrac{1}{{{{\left( {x – 1} \right)}^2}}} \ge 0\\
    {\left( {x – 1} \right)^2} \ne 0
    \end{array} \right. \Leftrightarrow x \ne 1\\
    2,\\
    1,\\
    a,\\
    ab + b\sqrt a  + \sqrt a  + 1\\
     = \left( {ab + b\sqrt a } \right) + \left( {\sqrt a  + 1} \right)\\
     = b\sqrt a .\left( {\sqrt a  + 1} \right) + \left( {\sqrt a  + 1} \right)\\
     = \left( {\sqrt a  + 1} \right)\left( {b\sqrt a  + 1} \right)\\
    2,\\
    \sqrt {9x + 9}  + \sqrt {x + 1}  = 20\,\,\,\,\,\,\,\,\left( {x \ge  – 1} \right)\\
     \Leftrightarrow \sqrt {9\left( {x + 1} \right)}  + \sqrt {x + 1}  = 20\\
     \Leftrightarrow 3.\sqrt {x + 1}  + \sqrt {x + 1}  = 20\\
     \Leftrightarrow 4\sqrt {x + 1}  = 20\\
     \Leftrightarrow \sqrt {x + 1}  = 5\\
     \Leftrightarrow x + 1 = 25\\
     \Leftrightarrow x = 24
    \end{array}\)

  2. Đáp án:

     

    Giải thích các bước giải:

    Bài 1.1:

    a)√81-√80.√0,2

    =9-4√5.1/√5

    =9-4=5

    b)√(2-√5)² -1/2.√20

    =√5 – 2 – 1/2.2√5

    =√5 – 2 – √5 =-2

    Bài1.2:

    a)√(-x+1) có nghĩa khi -x+1≥0

                                      ⇔x≤ 1

                      Vậy…

    b)√(1/x²-2x+1)

    ⇔  √(1/x²-2x+1)≥0    ⇔√(1/(x-1)²)≥0 ⇒ x≠1

      và    x²-2x+1≠0         và    (x-1)²≠0

    Bài 2.1:

    a)ab+ b√a +√a +1 (a≥0)

    =b√a(√a +1)+(√a+1)

    =(b√a +1)(√a +1)

    b)4a+1(a<0)

    =-4√a² + 1 (a<0)

    =1-(2√a)²=(1-2√a)(1+2√a)

    Bài 2.2:

    √(9x+9) +√(x+1) = 20 (ĐK:x≥-1)

    ⇔3√(x+1) +√(x+1) = 20

    ⇔√(x+1) . (3+1)=20

    ⇔√x+1 =5

    ⇔x+1=25⇔x=24(tmđk)

               Vậy…

Leave an answer